The Indian Ocean and US grand strategy : ensuring access and promoting security - Dombrowski, Peter J., 1963-; Winner, Andrew C.; Winner, Andrew C. (South Asia in world affairs series., 2014)
The Indian Ocean, with its critical routes for global commerce, is a potentially volatile location for geopolitical strife. Even as the region's role in the international economy and as a highway to conflict zones increases, the US has failed to advance a coherent strategy for protecting its interests in the Indian Ocean or for managing complex diplomatic relationships across the region. The Indian Ocean and US Grand Strategy presents a range of viewpoints about whether and how the US should alter its diplomatic and military strategies for this region. Contributors examine US interests in the.